Tinjauan Sosiologis Terhadap Tantangan Impelementasi Regulasi Wajib Belajar di Indonesia - Nurochman (Sekolah Tinggi Agama Islam (STAI) Ki Ageng Pekalongan, Indonesia, 2025)
This research contributes to the importance of cultural and political approaches in the development of faith-based educational institutions. This study aims to describe the sociological review related to the challenges of implementing Government Regulation No. 47 of 2008 on compulsory education in Indonesia. This qualitative research in the form of a literature study uses a descriptive approach. The research data uses various scientific literature that is correlated with the subject matter. Meanwhile, data analysis employs the stages of reduction, presentation, and verification. The findings of this study conclude that there are several issues posing challenges in the implementation of the Government Regulation on Compulsory Education in Indonesia, including cultural issues, the secularisation of education, the commercialisation of education, equity, and school examinations. This research contributes to the importance of sociological evaluation of the effectiveness of implementing regulations on compulsory education in Indonesian society.